PENGARUH RE-MAPPING ECU DENGAN VARIASI BUSI TERHADAP PERFORMA MESIN MATIC 150 CC - Ridwan Novianto; Sena Mahendra; Fahmy Zuhda Bahtiar; Diana Langgeng Mustikawati (Ivet University, 2025)
Technological advances in the automotive industry encourage humans to produce new innovations. including motorbikes with an EFI system. The EFI system at the factory is considered not to produce maximum power, therefore it is necessary to re-map the ECU on EFI system vehicles. The research results show that (1) The highest torque is when using racing spark plugs with a fuel mapping of 3%, an ignition angle of 1°, the torque increases by 11% at 4,000 rpm; (2) Highest power at 3% fuel mapping, 1° ignition angle with racing spark plugs, power increases 9% at 5,000 rpm; (3) The best SFC when using racing spark plugs and ECU remapping fuel at 5%, 2° ignition angle, achieves a reduction of 13% at 6,000 rpm; (4) In exhaust gas emissions, CO levels decreased by 59% in standard ECUs with racing spark plugs, the lowest CO2 in fuel mapping ECUs with 10% ignition angle 3° standard spark plugs, HC experienced the highest reduction of 15% with standard spark plugs in fuel mapping ECUs. 5% ignition angle 2°. The lowest O2 reduction is 40% when using ECU fuel mapping 3% ignition angle 1° standard spark plug.